2018
DOI: 10.1371/journal.pone.0200320
|View full text |Cite
|
Sign up to set email alerts
|

Largely different carotenogenesis in two pummelo fruits with different flesh colors

Abstract: Carotenoids in citrus fruits have health benefits and make the fruits visually attractive. Red-fleshed ‘Chuhong’ (‘CH’) and pale green-fleshed ‘Feicui’ (‘FC’) pummelo (Citrus maxima (Burm) Merr.) fruits are interesting materials for studying the mechanisms of carotenoid accumulation. In this study, particularly high contents of linear carotenes were observed in the albedo tissue, segment membranes and juice sacs of ‘CH’. However, carotenoids, especially β-carotene and xanthophylls, accumulated more in the flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…ABA is one of the downstream metabolites of carotenoids. Our previous reports showed that the ABA concentration was higher in pale-fleshed Feicui pummelo fruits than in red-fleshed Chuhong pummelo fruits at 150 DPA 25 . In addition, ABA has been reported to be involved in the regulation of lignin biosynthetic genes and TF regulators that respond to the lignin accumulation process in plants 34 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…ABA is one of the downstream metabolites of carotenoids. Our previous reports showed that the ABA concentration was higher in pale-fleshed Feicui pummelo fruits than in red-fleshed Chuhong pummelo fruits at 150 DPA 25 . In addition, ABA has been reported to be involved in the regulation of lignin biosynthetic genes and TF regulators that respond to the lignin accumulation process in plants 34 .…”
Section: Discussionmentioning
confidence: 87%
“…Citrus fruits, which are the most popular fruits worldwide, provide an assortment of functional components that are beneficial to human health, including flavonoids 19,20 , volatile compounds 21 , alkaloids 22 , and carotenoids [23][24][25][26] . However, in citrus fruit juice sacs, overaccumulation of lignin (a physiological disorder known as granulation) often occurs 9,10,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…1). The expression of CRTISO in different Citrus species does not correlate with the b,b-xanthophylls accumulation [12], and the characterization of citrus Z-ISO is restricted to pummelo (Citrus maxima) [29].…”
Section: Introductionmentioning
confidence: 97%
“…1). The expression of CRTISO during ripening has been analyzed in different Citrus species and does not correlate with accumulation of b,b-xanthophylls [12], and the characterization of citrus Z-ISO is very limited and restricted to pummelo (Citrus maxima), an ancient citrus species [29].…”
Section: Introductionmentioning
confidence: 99%
“…The Rohde Red Valencia is another sweet orange mutant with altered pigmentation, which shows an intense orange pulp associated to higher accumulation of β-cryptoxanthin and expression of PDS, ZDS and ZEP genes compared to parental cultivar [39]. Most of the sweet orange mutants with altered pigmentation display an intense pulp or peel coloration compared to ordinary cultivars due to attractiveness for breeders and consumers; however, research on varieties with defective fruit pigmentation is scarce and limited to other citrus species such as mandarins, pummelo or grapefruit [19,29,40,41,42,43,44]. A significant exception among sweet oranges is the mutant Pinalate, a spontaneous bud mutant from Navelate genotype.…”
Section: Introductionmentioning
confidence: 99%